The labor of talking to stay healthy and socially connected: Communication work during the COVID-19 pandemic - Erin E. Donovan; Renee Alducin; Kayleigh Spaulding; Joon Kim; Hussain Alkhafaji; Chloe Gonzales; Braidyn Lazenby; Anusha Naeem; Faiza Sarwar (Elsevier, 2022)
One of the primary means through which people protect themselves and their loved ones from COVID-19 is by communicating with others, as they discuss preventive health behaviors and make decisions about safe social interaction. These conversations are sometimes quite challenging. Guided by the conceptual lens of communication work, this study was an investigation of how communication during the pandemic was experienced by people as work. Findings validated and extended the communication work construct. Communication during the pandemic is effortful because it is high stakes, relentless, and takes an emotional toll. Nonetheless, many people feel a sense of responsibility and obligation to have these conversations. Communication about COVID-19 is divisible labor that can be shared. People engage in strategic preparation and message design to accomplish multiple goals before, during, and after discussions about pandemic topics.